(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2022)
The present work aimed to enhance the solubility and dissolution of the poorly water-soluble drug, sorafenib (SFN), by solid dispersion (SD) techniques. Solid dispersions of sorafenib were prepared by three different techniques, namely surface solid dispersions (SSD1-SSD15), melt granulation (MG1-MG15), liquisolid compacts (LSC1-LSC 9). All the formulations were evaluated for pre-formulation studies, solubility studies, percentage practical yield, % drug content, and in-vitro drug release. The best formulation based on drug release was further characterized for FTIR, XRD, SEM and stability studies. The formulations prepared by surface solid dispersions (SSD1-SSD15), melt granulation (MG1-MG15), liquisolid compacts (LSC1-LSC9) exhibited enhanced drug release compared to pure drug. Among all the formulations, sorafenib prepared by Melt Granulation technique (MG 3) showed highest drug release of 99.89%. The order of preference for solid dispersions prepared by different techniques was MG 3 > LSC 1 > SSD 3. The formulation MG 3 was further characterized for FTIR, where no significant changes were observed, suggesting no interactions between drug and excipients. X-ray diffraction studies revealed the conversion of sorafenib from the crystalline state to the amorphous, which was further supported by scanning electron microscopy. Stability studies proved the formulation was stable for 3 months. These findings suggest that the preparation of sorafenib solid dispersions using Melt Granulation technique could be a promising strategy for improvement of solubility and dissolution. Low cost, simple processing and great potentials in industrial production are the main advantages of this approach. In addition to enhancing the dissolution rate of poorly water-soluble drugs, this technique is also a fairly new technique to effectively retard drug release.